1999
DOI: 10.4315/0362-028x-62.6.619
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antioxidants and Gamma Irradiation on the Shelf Life of Beef Patties

Abstract: To improve the storage safety of two types of ground beef patty popular in Korea (general beef patties and bulgogi patties), we added various antioxidants (200 ppm; including butylated hydroxyanisole, ascorbyl palmitate, alpha-tocopherol, and beta-carotene) to typical formulations of patties, cooked the patties to 70 degrees C, and irradiated them at a dose of 1.5 or 3 kGy. During 30 d of storage at 5 degrees C, the number of aerobic bacteria and lactic acid bacteria were determined using total aerobic plate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 0 publications
5
9
0
Order By: Relevance
“…Also, the decreased in Fat content of above samples may be due to oxidation and hydrolysis by activity of microorganism, leading to the conversion of part of lipids into aldehydes, ketenes and other non fatty substances. As agree with [Anon, 2000;Du et al, 2001 andLee et al, 2005]. Mean while, the decreased in Bound water (B.W) of above samples were attributed to protein denaturalize according to [Silva and Chamul, 2000;El-Shourbagy, et al, 2003;Youssef et al, 2007 andKanatt, et al, 2009].…”
Section: Resultssupporting
confidence: 83%
“…Also, the decreased in Fat content of above samples may be due to oxidation and hydrolysis by activity of microorganism, leading to the conversion of part of lipids into aldehydes, ketenes and other non fatty substances. As agree with [Anon, 2000;Du et al, 2001 andLee et al, 2005]. Mean while, the decreased in Bound water (B.W) of above samples were attributed to protein denaturalize according to [Silva and Chamul, 2000;El-Shourbagy, et al, 2003;Youssef et al, 2007 andKanatt, et al, 2009].…”
Section: Resultssupporting
confidence: 83%
“…However, little is known about flavor profiles and consumers’ responses to specific characteristics of Bulgogi . Most studies on Bulgogi focused on developing Bulgogi menus for fast foods, a ready‐to‐eat meal, or food service operations (Park and Joo 1994; Kang and others 1998; Shin and others 2008), improving shelf life of Bulgogi products (Lee and others 1999; Jo and others 2003), or analyzing aroma compounds (Cho and others 2005; Ko and others 2006). Recently Hong and others (2007) examined consumer acceptability of Bulgogi with 100 consumers consisting of the U.S. native‐born citizens to develop Korean dishes acceptable for quick‐service Korean restaurant franchising operation in the United States, using a just‐about‐right (JAR) scale.…”
Section: Introductionmentioning
confidence: 99%
“…Yi, Lam, Yokoyama, Cheng, and Zhong () encapsulated β carotene by sodium caseinate (SC), whey protein isolate (WPI), and soybean protein isolate (SPI) by the homogenization‐evaporation method and found that cellular antioxidant activity of SC, WPI, and SPI nanoparticles was higher (60%) compared to β carotene alone (45%) in Caco‐2 cells. Lee, Yook, Kim, Lee, and Byun () added various antioxidants including β carotene to typical formulations of irradiated and nonirradiated patties and stated that all the natural antioxidants retarded lipid oxidation in cooked patties regardless of irradiation. However, Vara‐Ubol and Bowers () utilized sodium tripolyphosphate and β carotene in cooked ground turkey and ground pork and indicated that β carotene did not exhibit any antioxidant effect, but combination of β carotene with sodium tripolyphosphate delayed the oxidation of cooked ground pork up to the fourth day of storage 4 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The slight effects on 0th and 4th days may probably be based on the antimicrobial effect of chitosan. Lee et al () indicated that in control patties and patties with butylated hydroxyanisole that were irradiated at a dose of 1.5 kGy, growth of microorganisms appeared to be more rapid than in patties with natural antioxidants (ascorbyl palmitate, α tocopherol, and β carotene). Qin et al () wrapped pork meat patties with chitosan‐tea polyphenol composite film and found that the combination of chitosan and tea polyphenol effectively increased the effect of antimicrobial activity on meat patties.…”
Section: Resultsmentioning
confidence: 99%